Patent Foramen Ovale Closure for Treating Migraine: A Meta-Analysis - Yu Zhang; Haijiao Wang; Ling Liu (Journal of Interventional Cardiology)
Background. Observational studies have shown percutaneous patent foramen ovale (PFO) closure to be a safe means of reducing the frequency and duration of migraine. Objective. This study evaluated the efficacy and safety of PFO closure in patients with migraine using evidence-based medicine. Methods. The Pubmed (MEDLINE), Embase, and Cochrane Library databases were searched for randomized controlled trials (RCTs), cohort studies, and retrospective case series from January 1, 2001, to February 30, 2021. The Jadad scale and R 4.1.0 software were used to assess the quality of the literature and meta-analysis, respectively. Results. In total, three randomized controlled trials, one pooled study, and eight retrospective case series including 1,165 participants were included in the meta-analysis. Compared with control intervention in migraine, PFO closure could significantly reduce headache frequency (OR = 1.5698, 95% CI: 1.0465–2.3548, p=0.0293) and monthly migraine attacks and monthly migraine days (OR = 0.2594, 95% CI: 0.0790–0.4398, p=0.0048). Subgroup analysis of patients who all completed PFO surgery showed resolution of migraine headache for migraines with aura (OR = 1.5856, 95% CI: 1.0665–2.3575, p=0.0227). Conclusions. Treatment with PFO closure could reduce the frequency of headaches and monthly migraine days and is an efficient treatment for migraine attacks with aura.